Migration in Elista during the Restoration of the Kalmyk ASSR and the Return of Kalmyks from Places of Deportation. 1957–1963 - Sergey S. Belousov (Монголоведение)
Introduction. The period from 1957 to 1963 is an important period in the history of the city of Elista. In 1957 the autonomy of the Kalmyk people was restored, the statute of the capital city of the republic was returned to Elista, and the city itself received a powerful impetus for its further development. Since the city did not have its own resources for reconstruction, financial and other types of material assistance played the main role in this process from the state and population migrations organized by it. The great importance that population migrations had for Elista, the largest city in Kalmykia, makes it necessary to study this aspect in the past life of the city, which, moreover, was not specifically studied. The study aims to highlight the migration policy of the state during the years of the restoration of the republic and the most massive migrations in the history of the city, to show their impact on the development of the city. The article was prepared on the basis of documents of the state authorities of the Kalmyk ASSR, stored in the National Archive of the Republic of Kalmykia. The research was carried out based on historical-comparative and historical-genetic research methods. Results. In 1957–1963, there was a sharp surge in population migrations in Elista, caused by the restoration of Kalmykia as an administrative-territorial entity in 1957 and the granting of the city the legal status of its capital. The state allocated large funds for the restoration and further development of the socio-economic structure of the city, but there was a shortage of personnel and labor resources in general for the development of capital investments. To solve this problem, the authorities attracted Kalmyks returning from places of deportation to the city, conducted recruitment among workers from other subjects, invited military personnel demobilized by their army, and sent graduates of vocational schools to the city. As a result, the shortage of workers was largely overcome, which made it possible in 1964 to abandon new mass organized relocations to the city. Conclusions. The massive influx of population in 1957–1963 had a great impact on the demographic, social and national structure of the population. The population of Elista has increased dramatically, especially among young people, which has improved the demographic indicators of citizens, their social composition has changed, which has transformed into an urban one, the city has turned from a mono-national into a multi-national one.